2021
DOI: 10.1111/scd.12648
|View full text |Cite
|
Sign up to set email alerts
|

Mothers view about oral health status, oral hygiene behaviors, and dental services utilization of their children with hearing impairment attending special schools

Abstract: Aim: Parents are the principal decision-makers regarding their child's health. Awareness of mothers' view about their children's health, particularly with special health care needs (SHCN) (include hearing impaired children), is essential for health care providers. Therefore, the present study aimed to assess the mothers view about oral health status, oral hygiene practices, and dental services utilization of their children with hearing impairment attending special schools. Methods:A cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 12 Interestingly, Rajabloo et al recently reported that half of (49.2%) of hearing-impaired special need schools in Iran had a habit of brushing their teeth once daily. 28 The low oral hygiene practice in our study subjects might be due to socio-economic problems and/or lack of oral health awareness in our study participants. Our study also found that students who did not have family support while brushing their teeth were 5.1 times more likely to have dental caries than those who did have family support in their daily oral hygiene practice.…”
Section: Discussionmentioning
confidence: 85%
“… 12 Interestingly, Rajabloo et al recently reported that half of (49.2%) of hearing-impaired special need schools in Iran had a habit of brushing their teeth once daily. 28 The low oral hygiene practice in our study subjects might be due to socio-economic problems and/or lack of oral health awareness in our study participants. Our study also found that students who did not have family support while brushing their teeth were 5.1 times more likely to have dental caries than those who did have family support in their daily oral hygiene practice.…”
Section: Discussionmentioning
confidence: 85%